LABORATORY STUDY: WETTABILITY ANALYSIS OF SURFACTANT SOLUTION AND OIL IN SPONTANEOUS IMBIBITION TEST ON A CARBONATE RESERVOIR - THERESIA INDRIANI (NIM: 22215020), FANNY
Chemical flooding is one of enhanced oil recovery (EOR) method that incorporate chemicals to the injected water to increase oil recovery. Based on field applications, there have not been many successes. One of the reasons is the limited understanding of the chemical solutions criteria that match the characteristics of the reservoir. These criteria can be acquired by combatibility test, contact angle test, imbibition test, and coreflooding test. M Field is a carbonate reservoir. In the fabrication of carbonate artificial core,the writer made an artificial carbonate reservoir by mixing quartz sand, cement,and cutting with the composition of 30% of quartz sand, 40% of cement, and 30 of cutting. The results of this research shows that the artificial carbonate core observation of contact angle between formation water and surfactant solution towards the core surface, is known that T, C, and X surfactantscan improve the wettability of oil wet cores. From the imbibition tets showed that surfactant X 5% capable of producing the grearest RF, which is 100%. So, from the results of this study showed that the greater the concentration of surfactant solution can cause the greater the oil recovery, and the better the ability to improve the wettability. Core flooding performed by injecting one kind of efficient surfactant solution that pass the wettability and imbibition test. The solution that used is a surfactant X 2%.The core flooding experiment was done by an injection-soaking scenario. From this experiment is known that soaking time is needed to allow the imbibition process to cause a counter-flow between oil and surfactant X to make an injected surfactant X solution capable of producing oil in an area that has not been swept and finally increase the optimal recovery factor